ANALISIS PENGARUH STRATEGI EXPERIENTIAL MARKETING TERHADAP LOYALITAS NASABAH TABUNGAN PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK KANTOR CABANG SEMARANG - Sari, Nur Fitria; Sunindyo, Aris; Kodir, Moch. Abdul (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
This research”™s goal is to analyze the variable of experiental marketing”™s impact which include sense, feel, think, act, and relate regarding its relationship with saving customers”™ loyalty of PT Bank Tabungan Negara (Persero) Tbk Semarang Branch Office, which was done partially and simultaneously. Quantitative cause applied research was done using primary and secondary data, in which the former done using questionnaires with nonprobability sampling techniques applied with 100 respondents collected. The number of respondents were counted based on the calculation of lemeshow formula. While for the analytical methods, validity, reliability, and classic assumption tests were applied. For analysing the model, linear regression analysis was applied using t-test, F-test, and coefficient determination to test the hypotheses. As a result, sense, feel, and act variables have significant effect on savings customers”™ loyalty partially. On the other hand, relate and think variables have insignificant effect on savings customers”™ loyalty partially. All in all, the F-test shows that the variables have significant effect on savings customer”™s loyalty.